2008
DOI: 10.1186/1471-2164-9-550
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide and expression analysis of protein phosphatase 2C in rice and Arabidopsis

Abstract: Background: The protein phosphatase 2Cs (PP2Cs) from various organisms have been implicated to act as negative modulators of protein kinase pathways involved in diverse environmental stress responses and developmental processes. A genome-wide overview of the PP2C gene family in plants is not yet available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
272
2
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(300 citation statements)
references
References 80 publications
23
272
2
3
Order By: Relevance
“…A genome-wide and expression analysis of clade A PP2Cs in rice and Arabidopsis indicates that most of them were induced by ABA and drought stress or mannitol treatment, and the ABA response-related element (ABRE) motif was significantly enriched in the promoter region of them (Xue et al, 2008;Singh et al, 2010). Overexpression of the rice clade A PP2C gene OsPP2C108 in Arabidopsis enhanced the tolerance to salt, mannitol, and drought stresses, and sensitivity to ABA treatment (Singh et al, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A genome-wide and expression analysis of clade A PP2Cs in rice and Arabidopsis indicates that most of them were induced by ABA and drought stress or mannitol treatment, and the ABA response-related element (ABRE) motif was significantly enriched in the promoter region of them (Xue et al, 2008;Singh et al, 2010). Overexpression of the rice clade A PP2C gene OsPP2C108 in Arabidopsis enhanced the tolerance to salt, mannitol, and drought stresses, and sensitivity to ABA treatment (Singh et al, 2015).…”
mentioning
confidence: 99%
“…The rice genome contains 12 OsPYLs (Kim et al, 2012;He et al, 2014), 10 clade A PP2Cs (Xue et al, 2008), and 10 osmotic stress/ABA-activated protein kinases (SAPKs; Kobayashi et al, 2004). The molecular functions and interactions between some of these components were investigated in recent years.…”
mentioning
confidence: 99%
“…10 Protein phosphatase 2C (PP2C) type phosphatases function as regulators of various signal transduction pathways. 11 The best characterised PP2Cs are ABI1/ABI2 and related proteins that are central components in abscisic acid (ABA) signal transduction. 12 Interestingly, this transcript is moderately upregulated in IR (two-fold) but strongly downregulated in FL roots (five-fold).…”
Section: Different Cultivars As Tools To Study Salt Tolerancementioning
confidence: 99%
“…Moreover, these OsPP2Cs seem to also share roles with AtPP2CAs since they appear to be up-regulated in response to ABA and salt, similarly as AtPP2CAs (Xue et al, 2008), suggesting that OsPP2Cs might also be involved in ABA signaling. When looking for PYR/PYL/RCAR homologues in rice, 14 high identity genes popped up ( Figure 1B).…”
Section: Introductionmentioning
confidence: 99%
“…The overexpression approach of some of these elements, particularly of OsbZIP23 and OsbZIP72, has already been documented resulting in plants more tolerant to salinity and drought (Lu et al 2009;Xiang et al 2008). In the case of the OsPP2Cs, a comparative genome-wide overview of the PP2C family of Arabidopsis and rice, has revealed that both species have a similar number of genes encoding for PP2C proteins, as well as a similar number of PP2Cs classified as clade A, 9 and 10 respectively (Xue et al, 2008) ( Figure 1A).…”
Section: Introductionmentioning
confidence: 99%